Persepsi Masyarakat Tentang Representasi dalam Pilkada Tidak Langsung dan Dampaknya Terhadap Legitimasi Kepala Daerah Terpilih: (Studi Kasus : Jalan Taduan, Kec. Medan Tembung, Sumatera Utara) - Mhd Rizki Akbar; Parlaungan Gabriel Siahaan; Novridah Reanti Purba; Nur Azizaini Zhaharah; Cindy Aryani Putri; Putri Yasmin; Seniman Hati Zebua (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to build a complete picture of the relationship between the indirect regional election system, public perception of political representation, and the level of legitimacy of elected regional heads. Public perception of representation in indirect regional elections is the public's view of political representation in the election of regional heads by the DPRD and its influence on public recognition and trust in the elected regional heads. This legitimacy is the main foundation for regional heads to carry out their duties and authorities effectively. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through observation, interviews, and documentation of relevant sources. The number of respondents in this study was 5 respondents. The results of the study show that most people reject indirect regional elections because they are considered to reduce public participation and weaken the legitimacy of regional heads. Direct regional elections are considered more democratic, representative, and reflect the will of the people.